Functional organization of the human primary somatosensory cortex: A stereo-electroencephalography study. Issue 2 (February 2021) - Sun, Fengqiao; Zhang, Guojun; Ren, Liankun; Yu, Tao; Ren, Zhiwei; Gao, Runshi; Zhang, Xiaohua
Highlights: The sulcal cortex (BA2 and BA3) of human primary somatosensory cortex (S1) was studied by direct electrical stimulation. The general medial-to-lateral sequence of body representations within the entire S1 was identical to the Penfield homunculus. Several previously unreported somatosensory responses elicited from the sulcal cortex were delineated in this study. Abstract: Objective: The classical homunculus of the human primary somatosensory cortex (S1) established by Penfield has mainly portrayed the functional organization of convexial cortex, namely Brodmann area (BA) 1. However, little is known about the functions in fissural cortex including BA2 and BA3. We aim at drawing a refined and detailed somatosensory homunculus of the entire S1. Methods: We recruited 20 patients with drug-resistant focal epilepsy who underwent stereo-electroencephalography for preoperative assessments. Direct electrical stimulation was performed for functional mapping. Montreal Neurological Institute coordinates of the stimulation sites lying in S1 were acquired. Results: Stimulation of 177 sites in S1 yielded 149 positive sites (84%), most of which were located in the sulcal cortex. The spatial distribution of different body-part representations across the S1 surface revealed that the gross medial-to-lateral sequence of body representations within the entire S1 was consistent with the classical "homunculus". And we identified several unreported body-part representations from the sulcal cortex, such as forehead, deep elbow and wrist joints, and some dorsal body regions. Conclusions: Our results reveal general somatotopical characteristics of the entire S1 cortex and differences with the previous works of Penfield. Significance: The classical S1 homunculus was extended by providing further refinement and additional detail.